Hubungan Antara Pengetahuan Wanita Usia Subur Tentang Kanker Serviks Dengan Keikutsertaan Pemeriksaan Inspeksi Visual Asam Asetat - Ni Komang Puspita Dewi; Ni Nyoman Sumiasih; Ni Ketut Somoyani (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2019)
Cervical cancer is cancer that on second place cancer with high number of cases in Indonesia after breast cancer. The aim of this study was done to know relationship between knowledge of woman of childbearing age about cervical cancer with acetate acid visual inspection test participation. This study was correlational analytic research with cross sectional approach. Sample were about 47 woman of childbearing age. Statistical analysis used chi square test. Result that showed respondent’s knowledge include in good category about 51,1%. Respondent’s participation in acetate acid visual inspection test about 27,7%. Knowledge of woman of childbearing age about cervical cancer and acetate acid visual inspection test participation significantly associated with p 0,028 0,05. Knowledge of woman of childbearing age’s related with woman of childbearing age’s participation to do acetate acid visual. Health praties need to increase woman of childbearing age’s knowledge and support them to do acetate acid visual inspection test.Keywords: knowledge; cervical cancer; acetate acid visual inspection; participation